Pengaruh Kepemimpinan Transformasional Dan Lingkungan Kerja Non Fisik Terhadap Kinerja Karyawan Pada PT. Transco Energi Utama POM - Lidya Martha; Oki Nalia Fartika (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the effect of transformational leadership and non-physical work environment on employee performance at PT. Transco Energi Utama POM. The sample in this study amounted to 87 employees. The research data were collected from the results of multiple linear regression analysis and hypothesis testing. The results of this study indicate that transformational leadership has a positive and significant effect on employee performance, and the non-physical work environment has a positive and significant effect on employee performance. It can be seen that the significant value of transformational leadership and non-physical work environment on employee performance is the value 0.000 <0.05 and the t count is 3.637 from the t table 1.988.